Penerapan Etika Jurnalistik dalam Berita: Analisis Isi Etika Jurnalistik dalam Berita Selebritis Perempuan di Bangkapos.com - Putri, Sekar; Safril, Safril (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
News is not only about news value but news packaging that adheres to journalistic ethics and prioritizes media credibility as independent and trustworthy media. In practice, the media often prioritizes profit, resulting in a relaxation in applying the code of ethics in its writing. Bangkapos as a commercial media, presents a variety of informative and educative news. However, in the celebrity news column, especially female celebrities, based on the results of the analysis, media researchers do not apply the journalistic code of ethics in articles 4 and 8. News headlines tend to display women's sensitivity Keywords: News, Celebrities, Women, Code of Ethics